Old school - Kinney, Jeff (Kinney, Jeff. Diary of a wimpy kid (Series), 2015)
"Life was better in the old days. Or was it? That's the question Greg Heffley is asking as his town voluntarily unplugs and goes electronics-free. But modern life has its conveniences, and Greg isn't cut out for an old-fashioned world. With tension building inside and outside the Heffley home, will Greg find a way to survive?"--Provided by publisher.